Genetic detection of Theileria annulata from Bos taurus and Bubalus bubalis during health surveillance at marsh breeders' farm in Basra Marshes, Iraq. - Noor Hammed; Majid Bannai; Muna Jori (Basrah Journal of Veterinary Research)
In the context of health monitoring of a group of cattle and buffalo farms in marsh and swamp areas, these animals displayed evident clinical signs of nutritional deficiency in addition to symptoms that included high temperature (41 °C or higher), swollen lymph nodes, diarrhea, anemia, weakness, and decreased appetite. And, in some cases, cough. The presence of ticks in various areas of the body, especially the edges of the ear, the neck area and the area beneath the tail, indicated the possible presence of Theileriosis, a parasitic infection. Random blood samples were collected from sixteen individuals. Subsequently, DNA was extracted from these samples and Polymerase Chain Reaction (PCR) was utilized to amplify the small subunit of the 18S rRNA gene, which is highly specific for the detection of Babesia/Theileria species. The PCR procedure employed the GF (5'-G(C/T) (C/T) TTGT AAT TGG AAT GAT GG-3') and GR (5'-CCA AAG ACT TTG ATT TCT CTC-3') primers. The results were then compared to international isolates via an analysis of genetic nucleotide sequences using the Basic Local Alignment Search Tool (BLASTn) algorithm, available at the National Center for Biotechnology Information (NCBI). This analysis unveiled a significant genetic resemblance between the 18S rRNA gene sequences and T. annulata species, suggesting the presence of this parasite. As a consequential outcome of this study, it has been established that Bos taurus and Bubalus bubalis, can be a new host for T. annulata, particularly in the southern regions of Iraq.